Volume of Light Versus Moderate‐to‐Vigorous Physical Activity: Similar Benefits for All‐Cause Mortality?. Issue 7 (2nd April 2018) - Saint‐Maurice, Pedro F.; Troiano, Richard P.; Berrigan, David; Kraus, William E.; Matthews, Charles E.
Abstract : Background: It is unclear whether the greater benefits of moderate‐to‐vigorous physical activity (PA) over light PA are attributed to the higher‐intensity PA or simply the greater volume of PA accumulated per unit time for moderate‐to‐vigorous PA. We examined this question using estimates of the volume of light and moderate‐to‐vigorous PA in relation to all‐cause mortality. Methods and Results: We used National Health and Nutrition Examination Survey 2003–2006 accelerometer records in adults (≥40 years; n=4840) and mortality data collected through 2011 (n=700 deaths). We estimated intensity‐specific PA volume using activity counts (AC) accumulated in light (100–759 AC/min), moderate‐to‐vigorous PA (≥760 AC/min), and total PA (≥100 AC/min). We examined quartiles of each exposure using Cox proportional hazard models (hazard ratios [95% confidence interval) adjusted for demographic and behavioral risk factors, health status, and body mass index. Mortality risk was less across increasing quartiles of light PA volume (AC×1000) when compared with the least quartile (AC ≤61.8); the least risk occurred in the upper quartile of light PA, AC >98.5 (hazard ratios=0.69, 95% confidence interval: 0.47, 1.00, P trend ≤0.05). The benefits for mortality risk were greater across quartiles of moderate‐to‐vigorous PA and reached a hazard ratio of 0.28 (95% confidence interval: 0.17, 0.46, P trend ≤0.05) for AC >187.9, when compared with the referent group (AC ≤50.8). Results examining various combinations of light and moderate‐to‐vigorous intensity‐specific volumes demonstrated the strong influence of total activity on mortality risk. Conclusions: In this population, increasing light PA was associated with less mortality, but at an approximately equal volume of PA, moderate‐to‐vigorous PA appeared to have greater benefits.